2003
DOI: 10.4049/jimmunol.170.8.4111
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 Induces the Apoptosis of Resting and Activated Primary B Cells

Abstract: Cytokines play an important role in regulating the development and homeostasis of B cells by controlling their viability. In this study, we show that the recently described T cell-derived cytokine IL-21 induces the apoptosis of resting primary murine B cells. In addition, the activation of primary B cells with IL-4, LPS, or anti-CD40 Ab does not prevent IL-21-mediated apoptosis. The induction of apoptosis by IL-21 correlates with a down-regulation in the expression of Bcl-2 and Bcl-xL, two antiapoptotic member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(187 citation statements)
references
References 27 publications
(22 reference statements)
8
177
2
Order By: Relevance
“…Memory B cells respond more robustly than naive B cells in vitro to extrinsic stimuli such as CD40L, TLR ligands, and cytokines, as demonstrated by a shorter ttfd, greater proliferation, the generation of a greater number of plasmablasts, and increased Ig secretion (8, 10 -14). IL-21 has recently been recognized as a cytokine capable of inducing proliferation of human and murine B cells (23,30,32,33). Although a recent study presented data on the responses to IL-21 of naive B cells in CB and memory B cells in peripheral blood (PB), these cells were from different donors and tissues, hence quantitative comparisons of the responses could not be made (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Memory B cells respond more robustly than naive B cells in vitro to extrinsic stimuli such as CD40L, TLR ligands, and cytokines, as demonstrated by a shorter ttfd, greater proliferation, the generation of a greater number of plasmablasts, and increased Ig secretion (8, 10 -14). IL-21 has recently been recognized as a cytokine capable of inducing proliferation of human and murine B cells (23,30,32,33). Although a recent study presented data on the responses to IL-21 of naive B cells in CB and memory B cells in peripheral blood (PB), these cells were from different donors and tissues, hence quantitative comparisons of the responses could not be made (30).…”
Section: Discussionmentioning
confidence: 99%
“…(32,33). More recently, IL-21 was reported to deliver proapoptotic signals to B-CLL cells activated with CD40L (54).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that IL-21 plays an important role in the formation of GCs following immunization with T dependent Ags (17)(18)(19)(20). In vitro, stimulation with IL-21 and anti-CD40 can induce the differentiation of naive and memory B cells into isotype-switched B cells (21)(22)(23). These studies have demonstrated a role for IL-21 in B cell isotype switching and the formation of early PC and GC responses, but whether IL-21 is necessary for the development of long-term humoral immunity is not known.…”
Section: T He Development Of Ab Responses Occurs In Distinct Stagesmentioning
confidence: 99%
“…In humans, IL-21 is mainly produced by activated peripheral CD4 + T cells and follicular Th cells (21,22). IL-21 regulates B cell apoptosis, growth arrest, costimulation, and differentiation depending on the nature of the activation signals (23)(24)(25). For example, IL-21 induces maximum proliferation and produce Abs when costimulated with CD40L, but induces apoptosis when costimulated with anti-IgM in mice and human (19,26).…”
mentioning
confidence: 99%